Academic Senate Minutes 2015-03-12 - Academic Senate:::::::::
Chair Report. Agenda – Approved. Minutes of 2/26/15 – Approved. Revision to Computer Science major and minor – Approved. Theses Project, Public Nature policy approved. President Report. Provost Report. SAC Report. Vice Chair Report. Vice President of Administration and Finance Report. Associated Students Report. Vice President of Student Affairs Report. Resolution in Support of AS-3197-14, The Need for a Comprehensive California State University Policy on Academic Freedom approved. Statewide Senators Report. EPC Report. FSAC Report. CFA Report. Staff rep Report. Good of the Order.